Parents' Journeys to Acceptance and Support of Gender-diverse and Trans Children and Youth. (August 2020) - Pullen Sansfaçon, Annie; Kirichenko, Valeria; Holmes, Cindy; Feder, Stephen; Lawson, Margaret L.; Ghosh, Shuvo; Ducharme, Jennifer; Temple Newhook, Julia; Suerich-Gulick, Frank
Over the past 5 years in Canada, clinicians have observed an increasing number of gender-diverse and trans children and youth (GDTCY) accessing clinics for gender-affirming care. GDTCY who are able to access care are usually accompanied by their families, which provides a unique opportunity to integrate them into the treatment team. GDTCY have better health and social outcomes when strongly supported by their parents/caregivers. To optimize young people's health and well-being, it is essential that we learn more about family experiences in supporting their GDTCY and in overcoming barriers to accessing services. This project is one of the first qualitative studies that aims to develop a deeper understanding of GDTCY and their parents/caregivers' experiences of the gender-affirming care setting. This paper explores their journeys in coming to terms with their child's gender identity, including reactions to the child's coming out, struggles and facilitators of acceptance, and experiences in clinical settings.